Prognostic Utility of Right Ventricular Remodeling Over Conventional Risk Stratification in Patients With COVID-19 - Kim, Jiwon; Volodarskiy, Alexander; Sultana, Razia; Pollie, Meridith P; Yum, Brian; Nambiar, Lakshmi; Tafreshi, Romina; Mitlak, Hannah W; RoyChoudhury, Arindam; Horn, Evelyn M; Hriljac, Ingrid; Narula, Nupoor; et al. (Journal of the American College of Cardiology, 2020)
Coronavirus disease 2019 (COVID-19) is a growing pandemic that confers augmented risk for right ventricular (RV) dysfunction and dilation; the prognostic utility of adverse RV remodeling in COVID-19 patients is uncertain. The purpose of this study was to test whether adverse RV remodeling (dysfunction/dilation) predicts COVID-19 prognosis independent of clinical and biomarker risk stratification. Consecutive COVID-19 inpatients undergoing clinical transthoracic echocardiography at 3 New York City hospitals were studied; images were analyzed by a central core laboratory blinded to clinical and biomarker data. In total, 510 patients (age 64 ± 14 years, 66% men) were studied; RV dilation and dysfunction were present in 35% and 15%, respectively. RV dysfunction increased stepwise in relation to RV chamber size (p = 0.007). During inpatient follow-up (median 20 days), 77% of patients had a study-related endpoint (death 32%, discharge 45%). RV dysfunction (hazard ratio [HR]: 2.57; 95% confidence interval [CI]: 1.49 to 4.43; p = 0.001) and dilation (HR: 1.43; 95% CI: 1.05 to 1.96; p = 0.02) each independently conferred mortality risk. Patients without adverse RV remodeling were more likely to survive to hospital discharge (HR: 1.39; 95% CI: 1.01 to 1.90; p = 0.041). RV indices provided additional risk stratification beyond biomarker strata; risk for death was greatest among patients with adverse RV remodeling and positive biomarkers and was lesser among patients with isolated biomarker elevations (p ≤ 0.001). In multivariate analysis, adverse RV remodeling conferred a >2-fold increase in mortality risk, which remained significant (p < 0.01) when controlling for age and biomarker elevations; the predictive value of adverse RV remodeling was similar irrespective of whether analyses were performed using troponin, D-dimer, or ferritin. Adverse RV remodeling predicts mortality in COVID-19 independent of standard clinical and biomarker-based assessment.